Optical Coherence Tomography Angiography of Optic Disc in Eyes With Primary Open-angle Glaucoma and Normal-tension Glaucoma. Issue 3 (March 2019) - Toshev, Anani P.; Schuster, Alexander Karl-Georg; ul Hassan, Shahzada N.; Pfeiffer, Norbert; Hoffmann, Esther M.
Abstract : Purpose: To examine vessel density (VD) properties of the optic nerve head in eyes with ocular hypertension (OHT), high-tension glaucoma (HTG), and normal-tension glaucoma (NTG) and to evaluate associations on structural parameters of retinal nerve fiber layer (RNFL). Methods: Three groups of patients with OHT (n=15), HTG (n=36), and NTG (n=22), and a healthy control group (n=23) were included in this study. Peripapillary VD and optic disc flow area were measured using optical coherence tomography angiography, and peripapillary RNFL (pRNFL) thickness was determined. Global and sectoral analysis of optic nerve head vasculature and pRNFL thickness were measured. Results: Glaucomatous eyes had lower global peripapillary VD (HTG: 54.04±5.11, NTG: 54.74±6.37) compared with nonglaucomatous eyes (OHT: 59.72±1.63, controls: 61.35±2.47). VD parameters of the optic disc were comparable between the control and OHT group and between the HTG and NTG group. In the HTG and NTG groups we found significant correlations between average peripapillary VD and global pRNFL thickness (HTG ρ=0.71, P <0.001; NTG ρ=0.65, P =0.001). This was true for all sectors except for the temporal position. Conclusions: Overall, glaucomatous eyes had lower peripapillary VD compared with normal and OHT eyes. There is a strong relationship between the peripapillary structure of RNFL and its vasculature.